The Effect of the Group Investigation Model Assisted by the “Make a Match” Game on Mathematical Problem-Solving Ability in Statistics - Armina Rangkuti; Isran Rasyid Karo-Karo (MASI Mandiri Edukasi, 2026)
This study aimed to examine the effect of the Cooperative Learning model of the Group Investigation (GI) type assisted by the Make a Match game on students’ mathematical problem-solving ability in statistics. The study employed a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The sample consisted of 53 eighth-grade students, with 27 students in the experimental group and 26 students in the control group. Data were collected using an essay test of mathematical problem-solving ability that met the validity and reliability requirements (r₁₁ = 0.930). The data were analyzed using descriptive statistics, the Lilliefors normality test, the homogeneity test, an independent-samples t-test, and Cohen’s d effect size. The results showed that the mean posttest score of the experimental class was 83.78, compared with 78.96 for the control class. The t-test result showed a t-count of 2.190, which was greater than the t-table value of 2.008 at α = 0.05, indicating a significant difference between the two groups. The Cohen’s d value of 0.60 indicated a medium effect. Therefore, the Cooperative Learning model of the Group Investigation type assisted by the Make a Match game had a significant and practically meaningful effect on students’ mathematical problem-solving ability in statistics.